Hubungan Prestasi Kerja Pembantu Rumah Tangga, Kepuasan Majikan, Kemampuan Negosiasi dan Kerentanan Migran Wanita Pembantu Rumah Tangga Indonesia di Negara Tujuan (Studi Kasus di Wilayah Lembah Klang Selangor Malaysia) - Mindarti, Lely Indah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
This study examines the link between satisfaction and the ability of employers bargaining / negotiating with vulnerability migrant women domestic workers in the workplace employer. The study was conducted in Lembah Kelang Selangor Malaysia region, with a sample of 150 respondent employers who employ migrant female domestic workers from Indonesia and 150 female migrant domestic workers from Indonesia who was working in Malaysia. The results show significant relationship between work performance and ability to satisfy employers' bargaining/negotiating PRT. However, a negative relationship shows between satisfaction and the ability of employers bargaining / negotiating with vulnerability migrant women domestic workers in the workplace employer. An attempt to reduce vulnerability employers of domestic workers in the workplace is not enough with strengthening the legal and political protection. Important and strategic factor carried forward with efforts to increase domestic job performance itself